Growth, inequality, and poverty in rural China: the role of public investments [In Chinese] - Fan, Shenggen; Zhang, Linxiu; Zhang, Xiaobo (International Food Policy Research Institute, 2002)
In the past two decades, China has achieved world renown for reducing rural poverty. However, it is becoming harder to reduce poverty and inequality further in China, even though its economy continues to grow. This report compares the impact specific rural public investments can have on promoting growth and reducing poverty and inequality. Returns to these investments are calculated for the nation as a whole and for three economic zones in the west, central, and coastal regions of the country. Government expenditures that have the highest impact on poverty and growth include education, agricultural research and development, and rural infrastructure (roads, electricity, and telecommunications). Notably, spending on irrigation and anti-poverty loans had minimal impact. The report discusses the implications of these findings for setting future priorities for government investment. It also suggests avenues for future research and calls for a better understanding of how to improve the effectiveness of public resources. This report will be of interest to professionals involved in rural poverty reduction, rural development, agricultural growth, food security, and public investment policy.